„Es ist irritierend, unter etwas zu leiden, das keinen Schmerz verursacht“. Zu Stephan Thomes literarischen Auslotungen des prekären Begehrens - Drynda, Joanna (Studia Germanica Posnaniensia, 2015)
The essay is devoted to the novels of the German writer Stephen Thome. The writer’s narrative attention is focused on the puzzlement regarding intimate relations between males and females, aiming at captur-ing to what extent love, “a warming and intoxicating drug in the social coldness” (Volkmar Sigusch) is capable of making life meaningful. In the very centre of the analysis stands on the one hand the ‘in-each other-reflection’ of the male and female positions, on the other hand the palpable ambivalence between the inner freezing of the figures and their desire for gentle intimacy. The attempt has been made in order to open the arranged forms of the fulfillment of the desire – i.e. love and sexuality – to the possibility of depicting the phenomenon which is – according to Sigusch – significant for the late-modern era: more important than the sexual act for the partners is a steady relationship in which they feel accepted and preserved.